2010
DOI: 10.1007/s00464-010-1496-x
|View full text |Cite
|
Sign up to set email alerts
|

Transvesical peritoneoscopy with rigid scope: feasibility study in human male cadaver

Abstract: Background Transvesical port refers to the method of accessing the abdominal cavity through a natural orifice (i.e., urethra) under endoscopic visualization. Since its introduction in 2006, various reports have been published describing different surgical interventions using a rigid ureteroscope in a porcine model. The aim of this study was to test the access and feasibility of peritoneoscopy by using a rigid ureteroscope in a human male cadaver.Methods Two adult male cadavers were used to perform the procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Median time for the overall procedure, including establishment of the transvesical port, was 23 minutes (range [20][21][22][23][24][25][26][27][28][29][30]. Procedure time decreased with experience.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Median time for the overall procedure, including establishment of the transvesical port, was 23 minutes (range [20][21][22][23][24][25][26][27][28][29][30]. Procedure time decreased with experience.…”
Section: Resultsmentioning
confidence: 99%
“…Attempting to answer this question, Branco et al recently reported that peritoneoscopy and liver biopsy using a rigid ureteroscope through a transvesical port is feasible in a human male cadaver. 29 For bilateral varicocelectomy, one of the major problems of this route may be the length of the male urethra, because the flexible video cystourethroscope size is short. Probably, in the near future, biomedical engineering will need to develop longer scopes and instruments.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…The same group has also published further series to include transvesical transdiaphragmatic thoracoscopy as well combined transgastric-transvesical approaches to cholecystectomy [31] and nephrectomy [32]. Initial feasibility studies have also been performed in human cadaver [33] models. A case series of 60 human patients undergoing laparoscopic prostatectomy reported minimal contamination of the peritoneum following cystotomy, with positive bacterial cultures in 5 patients, however with no clinical significance and subsequent good recovery without further intervention required [34].…”
Section: Resultsmentioning
confidence: 99%
“…This might account for two cases of urethral laceration. This complication is not likely to happen in the human urethra as it easily holds tools up to 10 mm [23], but the risk of urethral stricture in transvesical procedures should nevertheless be assessed in humans.…”
Section: Discussionmentioning
confidence: 99%